2021
DOI: 10.1111/1440-1681.13489
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA H19 promotes myoblast fibrogenesis via regulating the miR‐20a‐5p‐Tgfbr2 axis

Abstract: Emerging evidence has indicated long non‐coding RNAs (lncRNAs) play important roles in diverse biological processes, including fibrosis. Here, we report that lncRNA H19 is able to promote skeletal muscle fibrosis. lnc‐H19 was identified to be highly expressed in skeletal muscle fibrosis in vivo and in vitro; while lnc‐H19 knockdown attenuated fibrosis in vitro. The knockdown of lnc‐H19 was proved to inhibit the activation of the TGFβ/Smad pathway in C2C12 myoblasts by sponging miR‐20a‐5p to regulate Tgfbr2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In this study, IF-C2C12-Exos were found to impair C2C12 differentiation and promote proliferation in vitro . In detail, decreased levels of MyoD, MyoG, and MYHC protein levels[ 25 , 26 , 40 ] suggesting that IF-C2C12-Exos reduced the myogenic differentiation ability of myoblasts. Induction experiments of myogenic differentiation also provided direct evidence for this result.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, IF-C2C12-Exos were found to impair C2C12 differentiation and promote proliferation in vitro . In detail, decreased levels of MyoD, MyoG, and MYHC protein levels[ 25 , 26 , 40 ] suggesting that IF-C2C12-Exos reduced the myogenic differentiation ability of myoblasts. Induction experiments of myogenic differentiation also provided direct evidence for this result.…”
Section: Discussionmentioning
confidence: 99%
“…CeRNA Network Prediction. The ceRNA network (consisting of DE-mRNAs, DE-miRNAs, and DE-lncRNAs) was constructed as previously described [12][13][14][15]. Interactions between DE-lncRNAs and DE-miRNAs were then confirmed using the miRcode database [16].…”
Section: Identification Of Fpi-associated Genes and Genementioning
confidence: 99%
“…LncRNAs share a common function of shape gene expression by titrating microRNAs (miRNAs), and this phenomenon was named competing endogenous RNA (ceRNA) [ 6 , 7 ]. For example, lncRNA H19, a 2.7-kb lncRNA, its ceRNA activities that modulate several miRNAs/genes aixes, including miR-20a-5p/transforming growth factor beta receptor 2, miR-216a−3p/actin alpha 2, miR-21/programmed cell death 4, and miR-19a/inhibitor of DNA binding 2, etc [ 8–11 ]. Simultaneously, elevated H19 expression is found in many cancer types, and therefore can be a potential therapeutic target in cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%